The Obstacles and Challenges of STEM Women Entrepreneurs - Debeljuh, Patricia (2022)
This  paper  analyzes  the  main  obstacles  and  challenges  that  women  face  in  STEM  entrepreneurship  and  gathers  the  results  of  the  research  carried  out  by  the  WISE  Project  (Women  in  STEM  Entrepreneurship),  developed  by  IAE  Business  School  and  BID Lab. The quantitative portion of this study examines 1100 cases, and the qualitative part  dissects  40  interviews  with  women  leaders  from  Argentina,  Peru,  Ecuador  and  Colombia,  identifiying  the  needs,  motivations  and  surveyed  expectations  of  female  entrepreneurs in STEM areas in 4 countries of the region.The main motivations for starting a business are the search for better work/life balance, the pursuit of self-realization, as well as the desire for freedom of choice; while obstacles include difficulty in generating the aforementioned balance, third-party prejudice, failed access  to  financial  resources,  risk  aversion  and  uncertainty  management.  A  positive  assessment  of  academic  training  for  entrepreneurial  activity  is  identified,  linked  to  technical  tools,  although  insufficient  in  topics  necessary  for  the  administration  of  a  business and in the development of managerial skills.The conclusions of this work seek to strengthen the ecosystem for entrepreneurship and innovation in STEM careers, not only by increasing the number of women who choose a STEM path, but also by encouraging new ventures that arise to take more disruptive approaches  in  business,  gain  access  to  adequate  financing,  boost  their  productivity,  grow in reach and size, and become job creators in their new economies.